Functional outcomes 6 months after severe traumatic brain injury following admission into intensive care unit: a cohort study in two tertiary hospitals - Mohamed Ludin, Salizar; Abdul Rashid, Nor'ain; Awang, Mohamed Saufi; Mat Nor, Mohd Basri (SAGE, 2019)
Severe traumatic brain injury (TBI) survivors show physical and functional improvements but continue to have cognitive and psychosocial problems throughout recovery. However, the functional outcome of severe TBI in Malaysia is unknown. The objective of this study is to measure the functional outcomes of severe TBI within 6 months post-injury. A cohort study was done on 33 severe TBI survivors. The Glasgow Outcome Scale–Extended (GOSE) was used in this study. The mean age of the participants was 31.79 years (range: 16-73 years). The logistic regression model was statistically significant, χ²(5, N = 33) = 29.09, p < .001. The length of stay (LOS) in incentive care unit (p = .049, odds ratio = 6.062) and duration on ventilator (p = .048, odds ratio = 0.083) were good predictors of the functional outcomes. Future research should focus on larger sample size of severe TBI in Malaysia